Implementasi Sistem Penentuan Jumlah Produksi Harian dengan Metode Weighted Moving Average pada Kantin Karyawan - Mohamad Ikhsan Komarudin; Dimas Abisono Punkastyo (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
Determining the right daily production quantity is a challenge for culinary MSMEs in employee canteens, where production decisions are often still based on subjective estimates, leading to discrepancies between production output and customer demand. Warung Mba Mong at the DFI Retail Nusantara employee canteen faces similar obstacles in determining daily production for gado-gado, ketoprak, and ketupat/lontong sayur, resulting in the risk of running out of menus or wastage due to leftover food. This study aims to design and build a website-based information system that applies the Weighted Moving Average (WMA) method to generate more measurable daily production recommendations based on historical data. The WMA method with six periods (n = 6) and weights of 6,5,4,3,2,1 was applied to monthly production recap data from January 2024 to December 2025. The forecasting results were disaggregated into daily recommendations by dividing the monthly forecast value by the number of effective working days. Forecasting accuracy was measured using the Mean Absolute Percentage Error (MAPE), yielding average values of 10.01% for gado-gado, 10.11% for ketoprak, and 12.36% for ketupat/lontong sayur, all falling into the "Good" category. The system was developed using the Extreme Programming (XP) method and tested using Black Box (Equivalence Partitioning) and White Box (Basis Path Testing) techniques, indicating that all functions performed according to specifications. This study proves that the WMA-based information system effectively helps the stall owner determine daily production quantities more objectively, thus reducing the risk of menu shortages and raw material waste.